How the food, beverage and alcohol industries presented the Public Health Responsibility Deal in UK print and online media reports. Issue 4 (8th August 2018) - Douglas, Nick; Knai, Cecile; Petticrew, Mark; Eastmure, Elizabeth; Durand, Mary Alison; Mays, Nicholas
Abstract: The Public Health Responsibility Deal (RD) in England is a public–private partnership between government, industry and other stakeholders aiming to improve public health in four key areas: food, alcohol, health at work and physical activity. Wider literature shows that industry engages in framing of public health policy problems, solutions and its role in solutions that is favourable to its interests. As part of an evaluation of the RD, we conducted a media analysis to explore how industry spokespersons (from commercial enterprises, trade associations and social aspects/public relations organisations) represented the RD in newspaper and online reports. We systematically searched databases indexing articles of British national newspapers and the online news services of national broadcasters for articles published between 2010 and 2015. After application of inclusion criteria, we identified 247 relevant articles. We extracted direct quotations by industry spokespersons and analysed them thematically. Media reporting about the RD provided industry spokespersons with a high-profile platform to present frames relating to food, beverages and alcohol that were favourable to advancing or protecting industry positions and agendas. Framing of issues addressed responsibility for public health problems, policy options and the role of industry, also legitimising industry spokespersons to advocate a position on how public health policy should evolve. Media analysis can elucidate industry discourses around public health and examine their engagement in framing to extend their influence in public health policy.